The Spectrum of Pulmonary Histomorphology Changes in COVID-19 Cases. (9th November 2022) - Ravikumar, V; Cool, C; Jing, J
Abstract: Introduction/Objective: Pulmonary specimens following COVID-19 virus infection demonstrate a spectrum of pulmonary histomorphology. Six patients with a history of COVID-19 infection are summarized in this review. The purpose of our study is to elucidate any possible correlations between clinical, laboratory, radiographic, and pathologic findings in COVID-19 patients. Further, we aim to characterize both non-specific and specific histomorphology and cytomorphology in COVID-19 patients. Methods/Case Report: Six patients with known COVID-19 infection and lung biopsies/resections are identified. A chart review is performed to collect clinical histories, the results of COVID-19 PCR testing, radiographic impressions, pathologic interpretations of histology, and clinical outcomes. Information is summarized and tabulated. Results (if a Case Study enter NA): The most common, non-specific histological findings are focal/diffuse acute lung injury, organizing lung injury, or a combination of both patterns. Unique features of COVID-19 infection are identified in three cases, which illustrate viral cytopathic changes within hyperplastic pneumocytes. These include basophilic, vacuolated, granular cytoplasm and variably sized cytoplasmic/nuclear inclusions. Virus-loaded pneumocytes are typically identified in the organizing phase, and rarely in the acute lung injury phase. Immunohistochemical staining of anti-nuclear capsule antibody with appropriate controls shows focal positive staining in one case. SARS-CoV-2 PCR is positive in formalin-fixed paraffin-embedded (FFPE) tissue, while a serum PCR assay is negative. Conclusion: The severity of clinical symptoms and clinical outcome are unrelated to the degree of lung involvement. Viral cytopathic changes are identified in three cases, with these specific findings associated with the organizing phase of lung injury, and either concurrent PCR positivity or positive immunohistochemical staining.